Evaluation of Mustard Genotypes Under Late Sowing Condition in the Southern Region of Bangladesh (Journal of Scientific Research, 2009)
The experiment was conducted to find out suitable mustard genotypes under late sowing condition for the southern region of Bangladesh. Ten genotypes of Rai groups were sown at five different dates (December 01, December 08, December 15, December 22 and December 29). The highest yield was obtained from December 01 sowing whereas the lowest yield was recorded from December 29 sowing. Ishurdi local and Pucca Rai produced higher yield of 924 kg/ha and 812 kg/ha, respectively and these two genotypes could be sown late up to December 15 for obtaining profitable yield. Keywords: Late sowing; Mustard genotypes; Sowing time; Screening. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.  DOI: 10.3329/jsr.v1i3.2576              J. Sci. Res. 1 (3), 667-672 (2009)